The knee a comprehensive review (World Scientific Pub. Co., 2010)
This book covers all the basics of the knee for practicing orthopedic surgeons and residents who are finishing their training and preparing for the board examinations. The text begins with chapters on the anatomy, physical examinations, and imaging, before proceeding on to pediatric considerations, arthroscopic techniques, ligament injuries, trauma, reconstructions, and the future of knee replacement surgery. There are many textbooks on the knee but no recent one has addressed the entire area of the knee from start to finish